The Fiscal and Financial Control Reform in Romania and Turkey: A Comparative Study - IONESCU, Luminiţa; BUHUR, Sami (Annals of Spiru Haret University. Economic Series, 2015)
After Romania became a member of the European Union in 2007, acquis communautaire became part of the Romanian national legislation and although Turkey is not a member of the EU, the accession process as a candidate country covers many sectors, such as: taxation, statistic, environment, financial control, etc. Since 2007 Romania recorded a strong economic growth, making best use of EU structural funds to enhance investment, innovation, and employment. Turkey is a candidate country and a strategic partner for the European Union with a dynamic economy. Turkey applied to join the European Economic Community in 1987 and it was declared eligible to join the EU in 1997. Finally, the accession negotiations were opened with Turkey in October 2005 and in the last years many reforms have been implemented. The aim of this paper is to present a comparative study between fiscal and financial control reform in Romania and Turkey, the evolution of fiscal and financial reforms in Romania, and the major problems seen in the public fiscal system in Turkey.